Network current quality enhancement under nonlinear and unbalanced load conditions using a four-wire inverter-based active shunt filter - Karim Belalia; Mohammed Khodja; Hamid Bouzeboudja; Azeddine Bendiabdellah; Abdelkader Mostefa (IAES Indonesian Section, 2021)
The flow of a large current in the neutral conductor of a transmission system is one of the major problems caused by harmonic pollution. This current can assume excessive values and even exceed the current flowing in the phases which can be extremely dangerous both for the equipment and the safety of the personnel. Currently, the parallel or shunt active filter (SAF) or parallel active filter is considered as the most effective solution to mitigate harmonic pollution and restore a sinusoidal current waveform in electrical distribution networks. The SAF can be used to compensate for harmonic currents, as well as that of the reactive power. This paper proposes a SAF circuit based on a four-arm inverter topology. The designed SAF is shown to lead to better harmonic compensation with a reduced THD (Total Harmonic Distortion) level in the presence of nonlinear and unbalanced loads in the network. The other goal of this study is to eliminate the neutral current caused by the unbalance in the polluting loads connected to the distribution network, achieve a near-sinusoidal current waveform and protect the electric network equipment.